Causes and Types of Bullying from Teachers Opinion - Khalf, Safaa Mohammed; Hussien, Hassan A (International Journal of Psychosocial Rehabilitation, 2020)
Bullying is old problem start from the beginning of humanity until yet in which it develop with new technologies to be more complex and difficult to diagnosis and deal with that give priority for researches concern with this topic because wide effects on peoples at all age stages. This study conduct to know the causes, and types of bullying that prevalence at Baghdad secondary schools at the period from 1st of November of 2019- to 10th march of 2020. A descriptive study data were analysis by use Statistical Package for Social Science (IBM-SSPS version 24) that found social causes were more causes for bullying from teachers opinion then come other causes adds to many types of bullying were prevalence at Baghdad secondary schools the first common types were verbal types.